The effect of anthropic fires on ant assemblage in the Cerrado of Southeastern Brazil - Oliveira, Tamires Camila Talamonte de; Santos, Kenia Aparecida dos; Nascimento, Gabriela Bandeiras do; Santiago, Graziele Santos (Revista Agrogeoambiental, 2022)
The Cerrado is the second largest biome in South America and due to its great species, richness, and environmental degradation, is considered a biodiversity hotspot. Fires in Cerrado can occur both naturally and through anthropic influence. However, due to the latter, the occurrence of fires has been increasingly frequent, as well as its impact on biotic communities. Ants’ colonies are widely used in studies of environmental impacts because of their responsiveness to environmental changes and easiness for their data to be analyzed. Here, the structure of the ants’ community in Cerrado environments at different areas post-fire times (two and four months, and a control area) in Itumirim, Minas Gerais, Brazil, was evaluated. Attractive baits were used as sampling methods, and found 48 species of ants belonging to 18 genera. Species richness was the same in all areas, showing that both two and four months after the fire occurrences seem to be enough to recover the ant population of these areas. Regarding ant composition, there were important differences, especially between the control area and the four months post-fire area. Moreover, vegetal biomass and vegetation covers only influenced ant composition. Here, it was found that species composition seems to be a better indicator of the responses of ant communities to post-fire effects, and can be used as a tool in monitoring programs.